Novo Nordisk talk: treatment for diabetes mellitus - what's new? / Zakiah Mohd Noordin and Assoc. Prof. Dr. Mahmathi Karuppannan - Mohd Noordin, Zakiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 3rd May 2023, Dr. Deepak Mukherjee, the Director of Clinical, Medical, Regulatory and Quality (CMRQ) from Novo Nordisk Pharma Malaysia, delivered a lecture at Dewan Kuliah 10, UiTM Puncak Alam campus. The lecture entitled "Treatment for diabetes mellitus - What's New?" was attended by more than 160 participants physically and through online streaming. The lecture session is a part of the diabetes topic activity under the PHC691 course (Applied Therapeutics in Gastrointestinal, Renal and Endocrine Disorders). It is aimed to enhance student's knowledge and understanding on the current and new pharmacotherapies available in the management of diabetes mellitus. Pharmacists play a critical role in the management of diabetes, as they are often the first point of contact for patients seeking advice and medication.